2012
DOI: 10.2188/jea.je20110068
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Coffee Consumption and Prevalence of Metabolic Syndrome Among Japanese Civil Servants

Abstract: BackgroundMetabolic syndrome has become a major worldwide public health problem. We examined the relationship between coffee consumption and the prevalence of metabolic syndrome among Japanese civil servants.MethodsThe study participants were 3284 employees (2335 men and 948 women) aged 20 to 65 years. Using data from their 2008 health checkup records, we analyzed the relationship between coffee consumption and the prevalence of metabolic syndrome. Metabolic syndrome was defined according to the Japanese crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 29 publications
3
49
0
4
Order By: Relevance
“…Finally, 11 published articles [23][24][25][26][27][28][35][36][37][38][39], including 13 studies with a total of 159,805 participants, were identified as eligible for the present meta-analysis of the relationship between coffee consumption with MetS risk. Of these, two articles [37,39] included two studies each; four studies were cohort studies with a total of 106,855 participants; eight studies were cross-sectional studies with 52,700 participants; and one was a case-control study with 250 participants. The detailed characteristics of the included studies are presented in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 11 published articles [23][24][25][26][27][28][35][36][37][38][39], including 13 studies with a total of 159,805 participants, were identified as eligible for the present meta-analysis of the relationship between coffee consumption with MetS risk. Of these, two articles [37,39] included two studies each; four studies were cohort studies with a total of 106,855 participants; eight studies were cross-sectional studies with 52,700 participants; and one was a case-control study with 250 participants. The detailed characteristics of the included studies are presented in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the dose-response analysis, data came from four articles [25,36,37,39] and included a total of 95,398 subjects. Evidence of a non-linear association was found (P non-linearity < 0.001) between coffee consumption and risk of MetS (Fig.…”
Section: Quantitative Synthesismentioning
confidence: 99%
“…Most of coffee's beneficial effects against type 2 diabetes are due to decaffeinated coffee (Pereira et al, 2006). Additionally, coffee drinking reduces the risk of Parkinson's disease (Webster, 2000), gallstone disease (Leitzmann, 1999), cardiovascular disease (Koizumi et al, 2011), dental plaque formation (Touger-Decker and van Loveren, 2003), high blood pressure (Matsuura et al, 2012). On the other hand, it increases the risk of cancer (Ames and Gold, 1998), raising levels of low-density lipoprotein or LDL (Ricketts et al, 2007), iron deficiency anaemia in mothers and infants (Muñoz et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing coffee consumption was found to be associated with a lower risk of metabolic syndrome in Japanese men, particularly in those drinking ≥ 4 cups per day (OR 0.61, 95% CI 0.39–0.95). The reduced rate of metabolic syndrome was due to an inverse association between coffee consumption and both blood pressure and triglyceride levels after controlling for other relevant factors 18 . Large population-based studies have also found that increasing coffee intake is associated with a lower incidence of diabetes 1921 .…”
Section: Analysis Of Clinical and Epidemiological Datamentioning
confidence: 87%